The Role of English Language Proficiency on Increase of Intercultural Communication Competence among International Postgraduate Students - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab (2015)
Postgraduate students from different national it ies and cultural backgrounds enrol at Malaysian universities to have better learning oppo11unities, and gain some new socia l and cultural skills. Students may a lso gain some essential competences through their contacts with their peers from different cu ltures, but some factors may affect their daily interactions. As Eng lish language is the main means of interactions among international stude nts of Malaysian universities, thus this study was conducted to examine the ro le of Eng li sh language profic iency (ELP) on increase of intercultural communication competence among international postgraduate students ofa Malaysian public university. A mixed methods research design which includes both of the quantitative and the qualitative methods was applied to conduct this study. This study had 120 participants from 17 different countries and based on their agreements 12 of them were interviewed to fu11her the information . The findings of this study confirmed that ELP is among the main factors that influence in teractions among postgrad uate stud ents from d iffere nt nationalities and their good levels of ELP helped them to improve their interc ultural communication competence and gain some new soc ial ski ll s. The results a lso illustrated that intercultural communication among postgraduate students from different countries helped them to improve the level of their ELP and find out some new strategies to deal with the different accents and s langs which use by students from different countries.